Optimalisasi Pengelolaan Zakat di Indonesia sebagai Instrumen Pengentasan Kemiskinan dan Pemberdayaan Ekonomi Umat - Alfian Abdul Bahij (Yayasan Al Ma'arif Dawuhan, 2026)
Poverty is a socio-economic issue that affects every nation, including Indonesia. Addressing poverty in Indonesia requires a synergistic approach that emphasizes community empowerment. The government has implemented various poverty alleviation policies; however, these programs remain ineffective as they primarily focus on economic growth rather than income distribution and tend to be consumptive in nature. Islam offers zakat as a viable solution to poverty alleviation. Beyond its religious significance, zakat serves as a socio-economic instrument that promotes equitable income distribution. Proper and efficient zakat distribution has the potential to alleviate poverty swiftly and effectively. A well-managed zakat system can contribute to resolving poverty-related issues and fostering social welfare by enhancing economic self-sufficiency within communities. This study highlights the role of zakat as a strategic tool for poverty reduction and its impact on achieving sustainable economic empowerment. Through a systematic and targeted approach, zakat can transform from a mere charitable obligation into an economic mechanism that supports the development of marginalized groups. The effectiveness of zakat in poverty alleviation underscores the importance of institutional frameworks and governance mechanisms to ensure transparency and accountability in its management. Therefore, integrating zakat into national poverty reduction strategies can serve as a complementary solution to conventional economic policies, promoting social justice and economic inclusivity. This paper emphasizes the need for further research on the optimization of zakat distribution to maximize its impact on poverty eradication and sustainable economic development in Indonesia.